The Effect of Profitability, Leverage, and Audit Quality on Earnings Management of Energy Sector Companies on the Indonesia Stock Exchange 2019-2023 - DEWI, Ni Kadek Sintiya Purnama; PRILIANDANI, Ni Made Intan; PUTRI, Putu Yudha Asteria; MANDALA, I Gusti Ngurah Agung Kepakisan (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to observe and explore every aspect listed on the IDX since 2019 - 2023. This problem arises because of the characteristics of profit manager actions and the inconsistency of the results of the initial study. The approach used is quantitative by applying panel data regression, including classical assumption tests, descriptive analysis, f tests, t tests, and testing the coefficient of determination. The total sample is 21 companies determined from a purposive sampling of 64 companies. The information is obtained from secondary sources, and panel data regression analysis is carried out using the Eviews tool. The study results if each independent variable contributes to earnings management. It shows that each aspect determined and selected in this study does not contribute to earnings management actions. This study shows that profitability, leverage, and audit quality have no significant effect on earnings management in energy sector companies on the IDX. Profitability and leverage do not determine earnings management practices, while audit quality is more utilized to increase investor confidence than to limit manipulation of financial statements.